Late Miocene ignimbrites at the southern Puna-northern Sierras Pampeanas border (~27°S): Stratigraphic correlation - Montero Lopez, Maria Carolina (2015)
New field observations and petrographic and geochemical data of pyroclastic deposits exposed along the Las Papas valley (border between southern Puna and northern Sierras Pampeanas, Argentina) and further north, lead us to propose a new stratigraphic correlation and classification of the late Miocene volcanism in this area. We redefine the Las Papas, Las Juntas, Aguada Alumbrera and Rosada ignimbrites and define the Agua Caliente and Del Medio ignimbrites. The whole set of ignimbrites are rhyolites and less frequently dacites of calc-alkaline affinity. In the present contribution we divide ignimbrites into the Agua Negra and Rincón groups, based mainly on their geochemical signature. The Agua Negra Group is formed by the Las Papas and Las Juntas ignimbrites, indurated and welded, lithic-rich, with crystal-poor pumices and crystal-rich matrix. The Rincón Group comprises the Agua Caliente, Aguada Alumbrera, Rosada and Del Medio ignimbrites, with variable welding degrees, lithic and crystal content. The greater enrichment of crystals in the matrix in comparison with the crystal content in pumices indicates significant elutriation during flow transport and thus volume estimations are to be considered lower bounds for the actual erupted volume. The total minimum estimated volume for the ignimbrites of the Agua Negra and Rincón groups is 2.8 km3 (2.3 km3 DRE). Field relationships and new analytical data indicate that the different acid ignimbrites that crop out in this small area are related to at least two different magma chambers. The widespread Quaternary volcanism in this area covers the older deposits, thus making it difficult to recognize the volcanic centers that produced these late Miocene ignimbrites.